2021
DOI: 10.7759/cureus.13871
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Efficacy of Telephone Medicine Consultations in Trauma and Orthopaedics During COVID-19 Using the Ashford Clinic Letter Score

Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, our aim was to protect staff and patients, therefore, face-to-face clinics were converted to telephone clinics. We retrospectively compared two groups of patients: those seen in traditional clinics pre-COVID-19 and those who had telephone clinics during the pandemic. The mean Ashford Clinic Letter Score (ACLS) for the face-to-face clinic letters was 6.7, and the letters from both groups of telemedicine appointments scored better; the first group scoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…However, across the two studies conducted with different participants through different timeframes there were conflicting results with Sibanda et al (2021) reporting that patients seen via telephone consultations during COVID scored significantly lower than those seen in-person during COVID (IPC: 7.967; TeC: 7.333; p<0.05). Whereas Raad et al (2021) reported that patients seen via telephone consultations during COVID scored significantly higher than those seen in-person pre-COVID (IPC: 6.7; TeC: 7.275; p<0.001).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, across the two studies conducted with different participants through different timeframes there were conflicting results with Sibanda et al (2021) reporting that patients seen via telephone consultations during COVID scored significantly lower than those seen in-person during COVID (IPC: 7.967; TeC: 7.333; p<0.05). Whereas Raad et al (2021) reported that patients seen via telephone consultations during COVID scored significantly higher than those seen in-person pre-COVID (IPC: 6.7; TeC: 7.275; p<0.001).…”
Section: Resultsmentioning
confidence: 94%
“…Eight studies were conducted in the USA and three in the UK (Natale et al 2022, Raad et al 2021, Sibanda et al 2021). Numbers of participants across the studies ranged from 33 (Lightsey et al 2021) to 535 (Uppal et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Teleconsultation remains frequent despite less stringent compliance with mask use and social distancing laws [4,59]. The increase in the use of telemedicine included both voice [88][89][90][91], multimedia [66,[92][93][94][95][96], video consultations [34,63,74,97] as well as videoconferences [13,[98][99][100][101][102][103][104][105]. Videoconferences ensure better patient identification and confirmation of the patient's identity without additional difficulties [106,107].…”
Section: Discussionmentioning
confidence: 99%
“…Telephone teleconsultation remains an essential and recognized means of providing remote medical services. Raad et al [90] observed that telephone clinics were practical and superior to traditional clinics for a specific set of patients during the pandemic. Estel et al [110] recommended orthopedic telemedical consultation because of the high acceptance, objective benefits, and similarity of clinical results with F2F visits.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Ashford Clinic Letter Scoring System (ACLS) to score clinic letters in an elective shoulder and elbow orthopaedic clinic. The ACLS tool has proven to be reliable, reproducible, and concise, which aids in objectively assessing and auditing the quality and efficacy of consultations [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%